2022
DOI: 10.3389/fphar.2022.848355
|View full text |Cite
|
Sign up to set email alerts
|

Shuxie-1 Decoction Alleviated CUMS -Induced Liver Injury via IL-6/JAK2/STAT3 Signaling

Abstract: Introduction: Chronic stress has been shown to cause liver damage in addition to psychological depression. Besides, drug-induced liver injury is frequently caused by antidepressants. Shuxie-1 decoction (SX-1) is a formula of traditional Chinese medicine commonly used in nourishing liver blood, and relieving depression. However, the underlying molecular mechanism remains unclear. Therefore, this study was designed to explore the effects and mechanisms of SX-1 in treating chronic stress-induced depression as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…In our study, a 1-week therapy with 18βGA (50 mg/kg) significantly diminished the concentration of hepatic enzymes ALT, AST, and ALP increased by chronic stress, proving that 18βGA may also repair hepatic damage. Our findings corroborate earlier studies on hepatic enzyme increase during CUMS [ 46 , 81 , 82 ]. Therefore, depression might be connected to liver damage, and that 18βGA can alleviate depressive-like behavior by suppressing the liver-brain inflammatory axis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, a 1-week therapy with 18βGA (50 mg/kg) significantly diminished the concentration of hepatic enzymes ALT, AST, and ALP increased by chronic stress, proving that 18βGA may also repair hepatic damage. Our findings corroborate earlier studies on hepatic enzyme increase during CUMS [ 46 , 81 , 82 ]. Therefore, depression might be connected to liver damage, and that 18βGA can alleviate depressive-like behavior by suppressing the liver-brain inflammatory axis.…”
Section: Discussionsupporting
confidence: 93%
“…To investigate the relationship between 18βGA and stress level, its effects on CORT and ACTH levels were investigated in CUMS animals. Increasing evidence also suggests that stress may harm the liver in addition to causing mental changes, with oxidative stress and inflammation possibly playing a role [ 46 ]. To comprehend the connection between chronic stress, neuroinflammation, and altered liver indicators, we also examined how CUMS altered liver enzymes and how 18βGA impacted the altered liver markers.…”
Section: Introductionmentioning
confidence: 99%
“…SX contains promising drug candidates that may prevent and treat colitis and reduce inflammation-related gastrointestinal dysfunction, such as Salvia miltiorrhiza ( Wen et al, 2013 ). In this study, we investigated the affinity of SX-major active components, baicalin (BAI) and paeoniflorin (PAE) ( Zhang et al, 2022 ), and oxidative stress response proteins using molecular docking techniques. Our results demonstrated high affinity binding between SX-related components such as BAI and PAE and the antioxidant response proteins, NQO1, HO1, p62, NRF2, and KEAP1.…”
Section: Discussionmentioning
confidence: 99%
“…Shu-Xie Decoction (SX) is an herbal formula developed by Dr. Shuyu Yang and colleagues using a combination of Suanzaoren Decoction and Huanglian Jiedu Decoction, also called Yangxue Rougan decoction. The quality and composition of the SX decoction was confirmed by UHPLC-QE-MS ( Zhang et al, 2022 ). SX is used in the First Affiliated Hospital of Xiamen University (Xiamen, China) for the management of diabetic patients with sleep disturbances, mood disorders, and gastrointestinal dysfunction, which are collectively referred to as a triad of ‘Shu-Xie.’ A previous study reported that SX suppresses inflammation and depression in mice ( Zhang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation